Pengaruh Kompetensi dan Independensi Terhadap Kualitas Audit dengan Motivasi dan Etika Auditor sebagai Variabel Moderasi (Studi Empiris Pada Kantor Akuntan Publik di Jakarta) - Ditia Ayu Karnisa; Anis Chariri (Diponegoro Journal of Accounting, 2015)
This study aimed to determine the effect of competence and independence on audit quality with motivation and ethics of auditors as moderating variablesThe population in this study is auditors who work in Public Accounting Firm (KAP) listed in the IAI (Institute of Accountants Indonesia) in Jakarta as much as 237 KAP. Samples were selected by purposive sampling technique with certain criteria : KAP at least has 3 partmers which resulted 43 respondents.The results of study showed that only competence affected audit quality. Meanwhile independence did not significantly influence audit quality. In addition, motivation and ethics audit did not moderate the relationship of competence and audit quality as well as the relationship of independence and audit quality.